Translation in cardiovascular stents and occluders: From biostable to fully degradable. Issue 2 (19th July 2017) - Huang, Yingying; Wong, Yee Shan; Ng, Herr Cheun Anthony; Boey, Freddy Y. C.; Venkatraman, Subbu
Abstract: Cardiovascular disease is a major cause of morbidity and mortality, especially in developed countries. Most academic research efforts in cardiovascular disease management focus on pharmacological interventions, or are concerned with discovering new disease markers for diagnosis and monitoring. Nonpharmacological interventions with therapeutic devices, conversely, are driven largely by novel materials and device design. Examples of such devices include coronary stents, heart valves, ventricular assist devices, and occluders for septal defects. Until recently, development of such devices remained largely with medical device companies. We trace the materials evolution story in two of these devices (stents and occluders), while also highlighting academic contributions, including our own, to the evolution story. Specifically, it addresses not only our successes, but also the challenges facing the translatability of concepts generated via academic research.